[3+2]-Cycloaddition of α-Diazocarbonyl Compounds with Arenediazonium Salts Catalyzed by Silver Nitrate Delivers 2,5-Disubstituted Tetrazoles - Chuprun, Sergey; Dar’in, Dmitry; Kantin, Grigory; Krasavin, Mikhail (Synthesis, 2019)
[3+2]-Cycloaddition of arenediazonium salts with diazo compounds (earlier exemplified only for trimethylsilyldiazomethane and 2,2,2-trifluorodiazoethane) has been developed to include a wide range of readily available α-diazocarbonyl compounds. The resulting 2-aryl-5-acyl-2H-tetrazoles are of high value in medicinal chemistry.
Keywords: α-diazocarbonyl compounds; arenediazonium tosylates; tetrazoles; [3+2]-cycloaddition; silver nitrate